Avaliação dos fatores angiogênicos, PIGF e sFLT-1, na pré-eclâmpsia - Fernanda Santos Mendes (2019)
Preeclampsia (PE) is an exclusively gestational and multisystemic disease. It is characterized by increased blood pressure (≥140 / 90 mmHg), with or without the presence of proteinuria, from the 20th week of gestation. The placenta is make an important role in the pathogenesis of this disease. During gestation, the placentation process releases important angiogenic factors, such as placental growth factor (PlGF), angiogenic factor, and soluble tyrosine kinase fms type 1 (sFlt-1), an antiangiogenic factor, that act during this process and throughout the course of gestation. Studies have shown that during a pregnancy with PE, the concentrations of PlGF decrease already in the beginning of gestation while those of sFlt-1 increase. And the ratio between these two concentrations may establish clues that help predict PE. In order to determine the importance of these levels and their efficacy in the prediction of PE, this study aimed to evaluate the concentrations of PlGF and sFlt-1 in pregnant women with PE and in the normotensive women performing a cross-sectional study and a longitudinal study. In the cross-sectional study of pregnant women with severe and normotensive PE, sFlt-1 levels were higher in pregnant women with severe PE (p <0.001), PlGF presented no difference, but the sFlt-1 / PlGF ratio was higher in with PE when comparing the two groups (p = 0.009). When dividing the PE group, both early and late, sFlt-1 levels were higher in both compared to normotensive levels (p <0.001). The values of PlGF were not different and the sFlt-1 / PlGF ratio was higher in pregnant women with early PE compared to normotensive women (p = 0.008). In the longitudinal study, we compared women who developed PE from those who did not develop in four gestational periods 12-19, 20-29, 30-34 and 35-40 weeks. In the women who developed PE, the concentrations of PlGF were lower in the gestational intervals 12-19 and 20-29 weeks (p = 0.023 and p = 0.003, respectively), sFlt-1 levels were higher in the range of 30 to 34 weeks (p = 0.025), and the sFlt-1 / PlGF ratio was higher in gestational periods 12-19 (p = 0.014), 20-29 (p = 0.036), and 30-34 (p = 0.025) in relation to pregnant women who did not PE. When comparing the concentrations of PlGF and sFlt-1, during gestational intervals, of the women who developed PE, PlGF was lower in the first weeks when comparing 12-19x 20-29 (p = 0.007) and 12-19x30-34 (p = 0.019). Comparison of sFlt-1 and sFlt-1 / PlGF ratios did not show significant differences in this group of pregnant women. The same comparison in the group that did not develop PE showed that PlGF levels were lower between weeks: 12-19x20 to 29 (p <0.001), 12-19x30-34 (p <0.001), 12-19x35-40 ( p = 0.01) and 20-29x30-34 (p = 0.043). The levels of sFlt-1 were increased in the comparison of the weeks: 12-19x30-34 (p = 0.01), 12-19x35-40 (p <0.001), 20-29x3540 (p <0.001) and 30- 34x35-40 (p <0.001). And the sFlt-1/PlGF ratio was lower between weeks: 12-19x20-29 (p = 0.001), 12-19x30-34 (p <0.001), 30-34x35-40 (p = 0.004). In view of these analyzes, PlGF proved to be a good predictive marker, sFlt-1 a good diagnostic marker and the sFlt-1/PlGF ratio can be considered both as a good predictive marker and as a good diagnostic marker. Longitudinal prospective studies containing more samples are required, with serial determination, for better analysis.